Notary Legal Remedies as Inside Authorities Registration and Registration of Commanditaire Vennootschap through the Administration System of Business Agencies - Masykur, Masykur; Yahya, Azhari; Dahlan, Dahlan (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
This study aims to explain the limits and responsibilities of the position carried out by the notary in registration of Commanditaire Vennootschap (CV) online through the business entity administration system. The research method used in this research is normative juridical using a statutory and conceptual approach. The collection of research materials is carried out by examining library materials or secondary data consisting of primary legal materials, secondary legal materials and tertiary legal materials. The results showed that the notary was only authorized and responsible for the creation of the deed of CV. Notary cannot receive power of attorney because it contradicts the UUJN which has been stipulated authority and responsibility attached to the position of a Notary. With the enactment of the Regulation of the Minister of Law and Human Rights of the Republic of Indonesia Number 17 of 2018. Registration of CV which was previously in the District Court is delegated to the Ministry of Law and Human Rights through the online system. The entire Notary is acting as an Authorized Officer not as an authorized official, there is a prosecution of an error in the registration process, then the Notary can indirectly be presented in the trial at the Court but it must be with the permission of the Notary Honorary Council. Thus the Notary can refuse to accept power over online CV registration via SABU, because in carrying out such registration a Notary must position himself as a person not as a public official. This is because it is not regulated in Law Number 30 of 2004 concerning the Position of Notary Public.Â